Hansenula polymorpha Pmt4p Plays Critical Roles in O-Mannosylation of Surface Membrane Proteins and Participates in Heteromeric Complex Formation. - Hyunah Kim; Eun Jung Thak; Dong-Jik Lee; Michael O Agaphonov; Hyun Ah Kang (PLoS ONE, 2015)
O-mannosylation, the addition of mannose to serine and threonine residues of secretory proteins, is a highly conserved post-translational modification found in organisms ranging from bacteria to humans. Here, we report the functional and molecular characterization of the HpPMT4 gene encoding a protein O-mannosyltransferase in the thermotolerant methylotrophic yeast Hansenula polymorpha, an emerging host for the production of therapeutic recombinant proteins. Compared to the deletion of HpPMT1, deletion of another major PMT gene, HpPMT4, resulted in more increased sensitivity to the antibiotic hygromycin B, caffeine, and osmotic stresses, but did not affect the thermotolerance of H. polymorpha. Notably, the deletion of HpPMT4 generated severe defects in glycosylation of the surface sensor proteins HpWsc1p and HpMid2p, with marginal effects on secreted glycoproteins such as chitinase and HpYps1p lacking a GPI anchor. However, despite the severely impaired mannosylation of surface sensor proteins in the Hppmt4∆ mutant, the phosphorylation of HpMpk1p and HpHog1p still showed a high increase upon treatment with cell wall disturbing agents or high concentrations of salts. The conditional Hppmt1pmt4∆ double mutant strains displayed severely impaired growth, enlarged cell size, and aberrant cell separation, implying that the loss of HpPMT4 function might be lethal to cells in the absence of HpPmt1p. Moreover, the HpPmt4 protein was found to form not only a homomeric complex but also a heteromeric complex with either HpPmt1p or HpPmt2p. Altogether, our results support the function of HpPmt4p as a key player in O-mannosylation of cell surface proteins and its participation in the formation of heterodimers with other PMT members, besides homodimer formation, in H. polymorpha.